Right Femoral Fragility Fracture in an Adolescent with Vitamin D Deficiency from COVID-19 Pandemic-Related Confinement - Suhasheni Rajendran; Ze Chen Lee; Chu Ee Seow; Chong Hui Khaw (Case Reports in Endocrinology)
Background. The COVID-19 pandemic has caused major impacts in various aspects of our life. In Malaysia, a Movement Control Order was imposed in March 2020. For almost two years, school going children and adolescents were not able to attend school physically, and their physical activity was confined within their room or house on most days. Case Description. We describe a case of a 14-year-old boy who was previously active in sports and sustained a low trauma fracture at the right neck of the femur following a prolonged period of extreme sedentary life along with poor dietary intake during the COVID-19 pandemic period. He underwent open reduction and screw fixation for the right neck femur fracture. He was thin with a low BMI (15.62 kg/m2) and a significant loss of muscle bulk in all limbs. Laboratory tests showed vitamin D deficiency (15.3 nmol/L) and the dual energy X-ray absorptiometry (DXA) showed a low Z-score for the total spine (−2.2) and total hip (−3.9). He was treated with activated vitamin D and vitamin D3 replacement. Sports physician was involved for individualized postoperative rehabilitation. Successive clinic visits showed remarkable improvements in physical fitness, sports participation, and normalization of vitamin D levels. Conclusion. A high degree of suspicion is needed to rule out secondary causes in adolescents who present with unusual fragility fractures.